2005
DOI: 10.1016/j.scriptamat.2005.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Damage accumulation during cyclic loading of a continuous alumina fibre reinforced aluminium composite

Abstract: Fibres fracture gradually during the fatigue cycling of continuous alumina fibre reinforced aluminium. The number of fibre breaks increases linearly with the logarithmic cycle number, depends on the maximum stress and the stress ratio, and agrees with published data for the fatigue of bare fibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Most of the experimental characterization of the mechanical behavior of continuous unidirectional alumina fiber reinforced aluminum that has been reported in the literature has focused on studies of the strength and deformation mechanisms of the composite loaded along the fiber axis. Compressive [23][24], tensile [25][26][27][28], bending [25], and fatigue [29] properties have been reported for loading applied along the fiber axis of unidirectional alumina fiber reinforced aluminum. Hall et al [30] studied the quasi-static and high strain rate properties of cross-ply unidirectional alumina reinforced aluminum MMC and found that the properties were strongly dependent on fiber distribution and alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the experimental characterization of the mechanical behavior of continuous unidirectional alumina fiber reinforced aluminum that has been reported in the literature has focused on studies of the strength and deformation mechanisms of the composite loaded along the fiber axis. Compressive [23][24], tensile [25][26][27][28], bending [25], and fatigue [29] properties have been reported for loading applied along the fiber axis of unidirectional alumina fiber reinforced aluminum. Hall et al [30] studied the quasi-static and high strain rate properties of cross-ply unidirectional alumina reinforced aluminum MMC and found that the properties were strongly dependent on fiber distribution and alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Some basic investigations about the fatigue behavior of continuous fiber reinforced light metals have been done by Baker, [7] Moser et al, [8] and Bettge et al [9] on silica and steel fiber [7] as well as on alumina fiber [8] reinforced aluminum and aluminum alloys, whereas ref. [9] focussed on silicon carbide reinforced titanium.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the bilinear stress versus number of cycles (S-N) model provides a much better representation of the data than the commonly used linear model for AI alloys. Moiser et al [13] investigated continuous alumina fiber reinforced aluminum composites under fatigue loading. Their experimental results showed that gradual fiber fractures were observed as the number of cycles increases.…”
Section: Introductionmentioning
confidence: 99%